The epidemiology of bacterial meningitis in the United States during 2008–2023: an analysis of active, laboratory, population-based, multistate surveillance dataResearch in context - Namrata Prasad; Miwako Kobayashi; Jennifer P. Collins; Amy B. Rubis; Gordana Derado; Miranda J. Delahoy; Daniel C. Payne; Lesley McGee; Sopio Chochua; Henju Marjuki; Lucy A. McNamara; LeAnne M. Fox; et al. (The Lancet Regional Health. Americas)
Summary: Background: Bacterial meningitis is a severe syndrome with dynamic epidemiology, but assessments of current trends are limited. We aimed to describe changing epidemiologic patterns among common bacterial causes of meningitis in the United States. Methods: We analyzed data on bacterial meningitis cases caused by Streptococcus pneumoniae, group B Streptococcus (GBS), Haemophilus influenzae, Neisseria meningitidis, and Listeria monocytogenes in 10 U.S. surveillance sites. We compared incidence (cases per 100,000) across four epidemiologic periods: 2008–2009, 2010–2019, 2020–2021, and 2022–2023. Findings: We identified 5,032 bacterial meningitis cases; among those with outcome data, 11% (573/5028) died. S. pneumoniae was the dominant pathogen (59% [2922/5032]) throughout. However, GBS predominated among infants aged 0–2 months (85% [660/775]), the age group with the highest incidence. Between 2008–2009 and 2010–2019, overall bacterial meningitis incidence declined from 1.3 to 1.1, driven by decreases in S. pneumoniae meningitis caused by serotypes contained in the 13-valent pneumococcal conjugate vaccine (PCV13) and N. meningitidis meningitis. Meningitis caused by non-b H. influenzae strains increased during this period. During 2020–2021, incidence declined to 0.7, driven by decreases in S. pneumoniae, H. influenzae, and N. meningitidis meningitis, regardless of organism subtype. During 2022–2023, incidence increased to 1.0, driven by increases in S. pneumoniae and H. influenzae meningitis. Case fatality ratios remained stable throughout. Interpretation: Bacterial meningitis incidence rates have declined since 2008, with a notable low during 2020–2021, followed by a resurgence during 2022–2023. Case fatality remains high. Strategies that provide effective and broader pneumococcal and H. influenzae serotype protection and prevent infant GBS meningitis could reduce residual meningitis burden. Funding: U.S. Centers for Disease Control and Prevention.